Influence of brassinolide in mitigating the adverse effect of drought on yield attributes in fenugreek (Trigonellafoenumgraecum Linn) genotypes (Indian Journal of Arid Horticulture, 2016)
Fenugreek (Trigonella foenum-graecum L.) is cultivated in India for multiple purposes, including as a vegetable, grain, and fodder. Fenugreek seeds are rich in an important steroid saponin called "Diosgenin," which is utilized in the synthesis of sex hormones and oral contraceptives. Water stress is a significant issue in India, where approximately 70% of cultivated land is rainfed. The application of brassinosteroids under abiotic stress conditions influences the hydrolysis of polysaccharides, leading to increased soluble sugars and enhanced resistance against environmental stresses, thereby improving crop productivity (Rao et al., 2002; Vidya Vardhini et al., 2006). While extensive research has been conducted on cereal crops under stress, there has been insufficient study on seed spices. This experiment was undertaken to investigate the role of brassinolide in mitigating the adverse effects of drought on yield attributes and varietal response in fenugreek genotypes.
Keywords: environmental stresses; fenugreek genotypes; crop productivity